SYNTHESIS NEODYMIUM (III) IMPRINTED POLYMERS (Nd-IPs) FOR SEPARATION AND ADSORPTION OF NEODYMIUM IONS FROM THE SOLUTION - Maulana, Anton
Neodymium (Nd) is a metal that has high economic value and widely used in various industrial fields as a source of new magnets, batteries, catalysts, increased production of crude oil and additives optics. Nd are found in the mineral Rare Earth Metals. Rare earth elements are not found in the free state in nature instead in the form of complex carbonate or phosphate. So, it requires separation process. In this research, Ion Imprinted Polymers (IIPs) material has been developed. This material can be used for adsorption of neodymium which is selective with high capabilities in recognizing ion. Ion imprinted polymer is a porous nano polymer that can bind and release ion. Polymerization occurs with the formation of bonds between monomers with a complex metal ions and ligands. Furthermore, the metal ions released from the polymer matrix, leaving the target metal ion molds. The IIPs have several advantages, such as the loss of analyte can be minimized, the amount of polymer used is relatively low (0.1-0.5 g), easy preparation, and high level of selectivity. Neodymium-Ion imprinted polymer (Nd-IPs) are synthesized through the formation of a ternary complex of yttrium ions with 5,7-dichoroquinoline-8-ol and 4-vinylpyridin and then carried toward polymerization with methyl methacrylate (MMA) as a monomer and ethyleneglycol dimethacrylate (EGDMA) as crosslinker in the 2-methoxy ethanol, initiated by 2,2-azobisisobutyronitrile (AIBN) at 80 ºC. Furthermore, metal ions are released using 0.1 M HCl to form the template. Next, Y-IPs are characterized by FTIR and SEM, with Non-Imprinted Polymers (NIPs) as a comparison. FTIR characterization showed that NIPs and Nd-IPs have successfully synthesized shown by the absence of a peak for the alkene functional group at 3000-3300 cm-1. It indicates the absence unreacted MMA and EGDMA. The existence of peaks on 754,17cm-1 in Nd-IPs before and after leaching showed that stretching vibration of –C–Cl groups derived from the DCQ. The wavenumber of –C=N from 1450,47cm-1 shift to 1454.33 cm-1 after leaching showed the group –C=N on vinylpyridin contribute to bond with the metal. SEM-EDS results showed that the Nd (III) ions have been successfully released from the polymer matrix in which there are 0.13% of Nd (III) ions before leaching while there are no Nd (III) ion presence in Nd-IPs after leaching. Characterization of retention properties performed by a batch method showed that the maximum adsorption capacity of Nd-IPs was 16.02 mg/g at pH 5 with a contact time of 30 minutes. Adsorption data have been analyzed using Langmuir and Freundlich adsorption isotherm. Adsorption of Nd (III) ions by Nd-IPs followed the Langmuir adsorption isotherm with a correlation coefficient of 0,9913. Pseudo first-order and pseudo second-order reaction kinetics Lagergren used to study the reaction kinetics adsorption process of Nd (III) by Nd-IPs. Based on the correlation coefficient, the adsorption kinetics of Nd (III) ions by Nd-IPs obeys pseudo second-order reaction kinetics. Based on thermodynamics data, adsorption process of Nd (III) ions by Nd-IPs take place endothermic with ?H of 14,67 kJ/mol, and the activation energy of 18.04 kJ/mol.